STRENGTHENING THE PRINCIPLE OF GOOD FAITH IN CONTRACT DISPUTE RESOLUTION IN INDONESIA - Ruchban, Dwi Hasrianty (Fakultas Hukum Universitas Kristen Indonesia Paulus, 2024)
In light of the rise of digital technology and internationalization, this research intends to investigate how the concept of good faith is being used and reinforced in Indonesian contract dispute resolution. An essential premise for the honest, open, and fair execution of contracts is the notion of good faith, as outlined in Article 1338 paragraph 3 of the Civil Code (KUHPer). The settlement of contract disputes must take into account the application of the norm of good faith in both offline and online contracts, due to the rise of electronic transactions governed by Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). Applying a qualitative analytical technique to primary, secondary, and tertiary legal sources, this research takes a normative legal stance. The research found that when people don't behave in good faith, it may affect the contract's legality, how the parties' rights and responsibilities are carried out, and how disputes are resolved. For contracts to be fair and afford parties more protection in the event of a disagreement, the concept of good faith must be strengthened.